Classical Club - Photographer Unknown (Webster University, 1941)
Black and white photograph of the Webster College Classical Club. This image includes eleven female students. All except one of the students are seated in desks. In the background are windows, bookshelves and classical busts. Gloria Meder is the third student from the right.